1983
DOI: 10.1177/1077727x8301100312
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility of Solar Home Heating Systems With Values, Felt Needs, and Past Experiences of Households

Abstract: A statewide survey was conducted to determine: 1. the perceived compatibility of solar systems to values, felt needs, and past experiences of households; 2. how perceptions of compatibility relate to the adoption of solar heating systems for the home; and 3. how various segments of the population differ in their evaluation of the compatibility of solar systems. Analysis of variance, with the Least Significant Difference Test, was used to analyze the responses from 912 households within the general population a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1984
1984
1987
1987

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Widespread use of this design technique decreases our nation's dependence upon fossil fuels and case studies have shown that it can be economical (Taylor, 1979). As indicated by Combs and Madden (1983), homebuyers may find solar homes more compatible with society's values yet incompatible with their own individual needs and preferences. The central question for this research then became: With such a strong rationale for its use, why is passive solar design in such an early adoption stage?…”
Section: Joan H Mclain-karkmentioning
confidence: 99%
See 1 more Smart Citation
“…Widespread use of this design technique decreases our nation's dependence upon fossil fuels and case studies have shown that it can be economical (Taylor, 1979). As indicated by Combs and Madden (1983), homebuyers may find solar homes more compatible with society's values yet incompatible with their own individual needs and preferences. The central question for this research then became: With such a strong rationale for its use, why is passive solar design in such an early adoption stage?…”
Section: Joan H Mclain-karkmentioning
confidence: 99%
“…Rogers and Shoemaker (1971) have found that adoption of any innovation is affected by how potential adopters perceive it as as being compatible with their own needs, values, and past experiences. As indicated by Combs and Madden (1983), homebuyers may find solar homes more compatible with society's values yet incompatible with their own individual needs and preferences. The implication is that solar designers have concentrated their r efforts in advancing the technology; yet, at the same time, they may not have adequately considered user preferences, thus impeding acceptance of the design.…”
Section: Joan H Mclain-karkmentioning
confidence: 99%
“…These studies include: the adoption of soil and water conservation practices in farming (Heffernan and Green, 1982;Lovejoy and Parent, 1982;Nowak, 1982;Taylor and Miller, 1978); the diffusion of earth-sheltered and/or solar energy systems (Combs and Madden, 1983;Combs et al, 1982;LaBay andKlnnear, 1981a, 1981b;Leonard-Barton, 1981a, 1981bLeonard-Barton, 1981b;McCray and Weber, 1981;Warkov, 1981); and the adoption of energy conservation practices in the home (Darley, 1978;Darley and Benlger, 1981).…”
Section: Diffusion-of-innovations Modelmentioning
confidence: 99%
“…The classical diffusion model-along with various modifications-has been used as a theoretical framework for a number of recent studies related to energy and environmental issues. These studies include: the adoption of soil and water conservation practices in farming (Heffernan and Green, 1982;Lovejoy and Parent, 1982;Nowak, 1982;Taylor and Miller, 1978); the diffusion of earth-sheltered and/or solar energy systems (Combs and Madden, 1983;Combs et al, 1982;LaBay andKlnnear, 1981a, 1981b;Leonard-Barton, 1981a, 1981bLeonard-Barton, 1981b;McCray and Weber, 1981;Warkov, 1981); and the adoption of energy conservation practices in the home (Darley, 1978;Darley and Benlger, 1981).…”
Section: Diffusion Refers To a Special Type Of Communication In Whichmentioning
confidence: 99%